The Influence of Leadership Style And Work Environment on Employee Performance Through Work Motivation in Indonesian Migrant Workers Protection Agency - Sugiharti, Ennyta; Subagja, Iwan Kurniawan, Sartono (Profesional Muda Cendekia Publishing, 2024)
Research Aims: Employee performance research is particularly intriguing because it incorporates individuals, the environment, processes, and equipment, as well as the organization's key goals. The goals of this study are to: (1) examine and analyze the impact of leadership style and work environment on work motivation; (2) examine and analyze the impact of leadership style and employee performance; (3) examine and analyze the impact of work environment on employee motivation; and (4) examine and analyze the effect of leadership style and work environment on employee performance through work motivation. Design/methodology/approach: The survey, which included 80 respondents, was conducted at the Office for the Protection of Indonesian Migrant Workers. The sampling methodology employs a saturated sample technique, as well as descriptive and path analytic tools. Research Findings: The findings revealed that (1) leadership style and work environment influence work motivation, (2) leadership style and work environment influence employee performance, (3) work motivation influences employee performance, and (4) work motivation does not influence leadership style and work environment influence employee performance. Work motivation, as an intervening variable, does not improve employee performance by changing leadership style and work environment. Theoretical Contribution/Originality: The research's originality stems from its application of a theoretical framework to a specific sector that is often overlooked in the broader literature on leadership and employee performance. Keywords: Leadership Style, Work Environment, Work Motivation, Employee Performance